2016
DOI: 10.1074/jbc.m115.705491
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fic (Filamentation Induced by cAMP) Protein from Clostridium difficile Reveals an Inhibitory Motif-independent Adenylylation/AMPylation Mechanism

Abstract: Filamentation induced by cAMP (Fic) domain proteins have been shown to catalyze the transfer of the AMP moiety from ATP onto a protein target. This type of post-translational modification was recently shown to play a crucial role in pathogenicity mediated by two bacterial virulence factors. Herein we characterize a novel Fic domain protein that we identified from the human pathogen Clostridium difficile. The crystal structure shows that the protein adopts a classical all-helical Fic fold, which belongs to clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 67 publications
0
38
0
1
Order By: Relevance
“…Though the surfaces involved in oligomerisation of this class III Fic protein are different from that of FICD, these two repressive mechanisms converge on the state of their α inh s. As such, divergent Fic proteins potentially exploit, for regulatory purposes, an intrinsic metastability of this structurally conserved inhibitory α‐helix (Garcia‐Pino et al , ). Interestingly, the more extensive dimerisation surface of FICD (which contains Leu258 and is situated at the boundary of the Fic domain core and the N‐terminal Fic domain extension) also acts as a structurally conserved dimer interface in other class II bacterial Fic proteins: CdFic (Dedic et al , ) and Bacteroides thetaiotaomicron (BtFic; PDB: 3CUC), but not in the monomeric Shewanella oneidensis Fic (SoFic) protein (Goepfert et al , ). Moreover, a His57Ala mutation in dimeric CdFic (which is structurally equivalent to FICD K256A ) causes increased solvent accessibility and auto‐AMPylation of a region homologous to the loop linking FICD's Glu242‐helix and the α inh (Dedic et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Though the surfaces involved in oligomerisation of this class III Fic protein are different from that of FICD, these two repressive mechanisms converge on the state of their α inh s. As such, divergent Fic proteins potentially exploit, for regulatory purposes, an intrinsic metastability of this structurally conserved inhibitory α‐helix (Garcia‐Pino et al , ). Interestingly, the more extensive dimerisation surface of FICD (which contains Leu258 and is situated at the boundary of the Fic domain core and the N‐terminal Fic domain extension) also acts as a structurally conserved dimer interface in other class II bacterial Fic proteins: CdFic (Dedic et al , ) and Bacteroides thetaiotaomicron (BtFic; PDB: 3CUC), but not in the monomeric Shewanella oneidensis Fic (SoFic) protein (Goepfert et al , ). Moreover, a His57Ala mutation in dimeric CdFic (which is structurally equivalent to FICD K256A ) causes increased solvent accessibility and auto‐AMPylation of a region homologous to the loop linking FICD's Glu242‐helix and the α inh (Dedic et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…42 Structural analysis also revealed that the ineffectiveness of the autoinhibitory helix of CdFic is due to structural changes in the active site of the Fic domain. This results in changes to the positioning of ATP in the ATP binding pocket 42 (Figure 14). The α and β -phosphates of ATP are repositioned by formation of a new salt bridge formation between Arg-200 of CdFic and the α -phosphate of ATP.…”
Section: Regulation Of Fic Domainsmentioning
confidence: 99%
“…The α and β -phosphates of ATP are repositioned by formation of a new salt bridge formation between Arg-200 of CdFic and the α -phosphate of ATP. 42 In other known Fic domains, this position is usually a hydrophobic residue. This repositioning allows for the accommodation of the γ -phosphate in the anion hole despite the presence of the conserved autoinhibitory helix, supporting the idea that AMPylation of other targets may not be inhibited.…”
Section: Regulation Of Fic Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In less than a decade, FIC proteins have emerged as a large family of enzymes controling the activity of target proteins by post-translationally modifying them with phosphate-containing compounds (reviewed in 1,2, 3, 4 ). These proteins are characterized by the presence of a conserved FIC domain, which carries out the post-translational modification (PTM) of a Tyr, Ser or Thr residue in a target protein 5, 6, 7, 8, 9, 10, 11 . The most frequent PTM reaction catalyzed by FIC enzymes is the addition of AMP using ATP as a cofactor, coined AMPylation or adenylylation.…”
Section: Introductionmentioning
confidence: 99%